STRANGE EROS: REVERBERATIONS OF THE UNUSUAL IN CLARICE LISPECTOR’S NARRATIVES: REVERBERATIONS OF THE UNUSUAL IN CLARICE LISPECTOR’S NARRATIVES (Muitas Vozes, 2021)
This paper presents a reading of some short stories of Clarice Lispector in which erotic or loving themes are manifested with narrative solutions that express the strange or unusual of fiction. The combination of strangeness and eroticism results in a possible/impossible subjective reconfiguration of characters which come across the “most concrete from themselves”, achieving in fiction the Georges Bataille’s maxim (2004), to whom eroticism is what “puts the being into question”. Reframing the gender endowments, the perception of herself and the relation with the Other, the occurrences of the unusual erotic are a relevant component of the Clarice’s way of narrating sexual themes in her fiction.